1987
DOI: 10.1002/j.1537-2197.1987.tb08671.x
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Filament Elongation in Ipomoea Nil (Convolvulaceae)

Abstract: It has been thought for some time that morning glory filaments elongate in response to changes in concentrations of gibberellins (Murakami, 1973), but many other aspects of their growth have remained unstudied. In the present work, the interacting roles of gibberellin and ethylene in filament growth were examined. Filaments elongated ten‐fold by epidermal cell elongation accompanied by ten‐fold increases in fresh and dry weight. Applied gibberellins could stimulate filament growth in vitro, but gibberellin bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Research has shown that high-temperature treatments reduce ethylene production from filaments alone and from filaments with anthers attached (Biddington and Robinson 1993). The ethylene precursor ACC inhibited filament growth in Fuchsia hybrida at 32 ∘ C (Jones and Koning 1986) and of Ipomoea nil at 30 ∘ C (Koning and Raab 1987). Compared with the control, the high temperature treatment reduced the endogenous hormone content of IAA in rapeseed plants (Zhou and Leul 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that high-temperature treatments reduce ethylene production from filaments alone and from filaments with anthers attached (Biddington and Robinson 1993). The ethylene precursor ACC inhibited filament growth in Fuchsia hybrida at 32 ∘ C (Jones and Koning 1986) and of Ipomoea nil at 30 ∘ C (Koning and Raab 1987). Compared with the control, the high temperature treatment reduced the endogenous hormone content of IAA in rapeseed plants (Zhou and Leul 1999).…”
Section: Discussionmentioning
confidence: 99%
“…see Métraux 1988, Katsumi andIshida 1991). Also, GAs were shown to promote stamen filament growth in many, but not all, species (Greyson and Tepfer 1967, Koevenig 1973, Koning and Raab 1987. The similarity in GA and low temperature response suggests that the possible changes in the MS33 product caused by the latter may promote GA biosynthesis or GA signal transduction pathway, which in turn triggers cell elongation.…”
Section: Effects Of Low Temperature and Gibberellic Acid On Filament mentioning
confidence: 99%
“…Endogenous plant growth substances (PGSs), e.g., gibberellins (GAs), ethylene, and indole-3-acetic acid have been shown to influence the growth of stamens, in particular stamen filaments, and petals in various species (Schaeverbeke 1965;Greyson and Tepfer 1967;Koevenig 1973;Koning and Raab 1987;Kiss and Koning 1990). These studies suggest that a multifactoral control mechanism is responsible for normal stamen development.…”
mentioning
confidence: 98%